PENENTUAN NILAI SUN PROTECTION FACTOR (SPF) EKSTRAK ETANOL RIMPANG BANGLE (Zingiber purpureum Rovb.) SECARA SPEKTROFOTOMETRI UV-Vis - Yusriyani; sukirawati, sukirawati (Jurnal Kesehatan Yamasi Makassar, 2023)
Research has been conducted on the determination of the value of Sun Protection Factor (SPF) extract of rhizome bangle (Zingiber purpureum Roxb.) in spectrophotometer UV-Vis As an active ingredient of sunscreen. This study aims to determine the SPF value using the UV-Vis spectrophotometry method. Rhizome bangle extracted by maceration method using 96% ethanol solvent, then made in a concentration of sample solution 10 ppm, 20 ppm, 30 ppm 40 ppm and 50 ppm. The solution was then measured for absorbance in a UV-Vis spectrophotometer with a wavelength of 290-320 and an interval of 5 nm. Calculation of SPF values using the Petro method, and the results of the study showed that rhizome bangle extract had activity as a dark veil with a minimum level of protection sun protection at a concentration of 20 ppm with a value of SPF 3,60003. A concentration of 30 ppm shows extra protection with an SPF value of 6.30566. The concentration of 40 ppm showed maximum protection with a value of SPF 9,38396 and a concentration of 50 ppm indicating ultra-protil with a value of SPF 28,10936. Based on the results of these tests also obtained a linear relationship between concentration and SPF value.